2023
DOI: 10.12688/hrbopenres.12837.3
|View full text |Cite
|
Sign up to set email alerts
|

Promoting men’s awareness, self-examination, and help-seeking for testicular disorders: a systematic review of interventions

Mohamad M. Saab,
Martin P. Davoren,
Aileen Murphy
et al.

Abstract: Background: Testicular cancer (TC) is among the most commonly diagnosed cancers in men aged 15–40 years. The incidence of TC is on the rise. Benign testicular disorders, such as testicular torsion and epididymitis, can lead to testicular ischemia, sepsis, and infertility if left untreated. This updated systematic review aims to evaluate the effectiveness of studies promoting men’s knowledge and awareness of testicular disorders and/or self-examination, behaviours and/or intentions to examine their testes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Offline communication, a conventional way of delivering health information, can reach out to a wider population, particularly individuals who do not use social media, as well as older men and men who have low literacy and/or health literacy levels 45 . Traditionally, testicular cancer awareness campaigns have been delivered offline, with well‐documented evidence of effectiveness, albeit in the short‐term 20,22 . Engaging at‐risk younger groups with a testicular awareness campaign requires outside‐the‐box thinking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Offline communication, a conventional way of delivering health information, can reach out to a wider population, particularly individuals who do not use social media, as well as older men and men who have low literacy and/or health literacy levels 45 . Traditionally, testicular cancer awareness campaigns have been delivered offline, with well‐documented evidence of effectiveness, albeit in the short‐term 20,22 . Engaging at‐risk younger groups with a testicular awareness campaign requires outside‐the‐box thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews conducted over the past decade have reported on studies that explored and aimed to enhance men's awareness of testicular cancer and self‐examination 19–22 . Conversely, very little is known about men's awareness of benign testicular diseases 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective implementation of preventive measures relies on raising public awareness, understanding symptoms and risk factors, and regular self-examination of the testes [16]. Emphasizing the simplicity and cost-effectiveness of TSE, the American Cancer Society advocates for its inclusion as a fundamental aspect of routine cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from six systematic reviews conducted between 2015 and 2023 indicate that men's awareness of testicular diseases (particularly benign testicular diseases), intentions to seek help for symptoms of concern and behaviours in terms of performing testicular self-examination were all suboptimal [12][13][14][15][16][17]. The latest of these reviews found that several interventions were successful in increasing men's awareness of testicular cancer and testicular self-examination, including 'a PowerPoint presentation, an online educational brochure, video-assisted teaching, a motivational video, and a virtual reality game' (p. 2) [17]. However, only one study addressed help-seeking for testicular symptoms and aimed to promote men's awareness of both malignant and benign testicular diseases [18].…”
Section: Introductionmentioning
confidence: 99%